The people's Jesus : trajectories in early Christianity - Scroggs, Robin; Johnson, Marshall D. (Minneapolis : Fortress Press, 2011)
"Seeking the patterns of thought that shaped early beliefs about Jesus as the Christ, the late Robin Scroggs explores the social settings that sparked the primary christological themes and traces their trajectories through the literature that made up the New Testament" -- Publisher's description.
The cosmocrator trajectory -- The Son of Man trajectory: early stages -- The Christos trajectory -- The fate of Christos in the Hellenistic church -- The three trajectories: what's at stake for believers -- The Synoptic Gospels and the three trajectories -- Paul and the cosmocrator trajectory -- The cosmocrator trajectory in Colossians and Ephesians -- Hebrews and the cosmocrator trajectory -- Theology and politics: Acts and Revelation -- The Gospel and First Epistle of John and the three trajectories.
Includes bibliographical references and index.
Keywords: Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Bible. -- Theology; Bible. -- Social scientific criticism